KAJIAN LEBAR RETAK BALOK BETON AKIBAT PENGGUNAAN TULANGAN ALUMINIUM PADUAN - Novi Rahmayanti; Iman Satyarno (TEKNISIA, 2015)
The use of concrete structures in a corrosive environment requires a minimum concrete cover thickness of 50 mm.Tthick concrete cover is certainly very risky occurrence of spalling which result in reduced capacity of the cross section of the structure. For this study utilizes the aluminum alloy material as additional reinforcement bars that fill a third of thick concrete cover, where the aluminum has properties that are resistant to corrosion. The purpose of this study to obtain the contribution of aluminum alloy in the capacity of the concrete beam section and a wide crack that occurs without using reinforcement rebars. This study uses five pieces of beam specimen dimensions of 300 mm x 150 mm and a span length of 1600 mm. The beam using materials mortar, concrete and 13 mm diameters of aluminum alloy that were tested for bending strength. As for each of the aluminum ratio of 0% (B0); 0.34% (B1); 0.68% (B2); 1.02% (B3) and 1.36% (B4). Testing method requiring a single point of loading. The results showed that the load capacity of the test specimen when the first crack in the beam but not significantly increased with increasing amount of aluminum, which is equal to 1 times, 1,002 times, 1.01 times, 1.03 times and 1.07 times the beam ratio aluminum 0%. The maximum load capacity has increased along with increasing the number of aluminum, which is equal to 1 times, 1.64 times, 2.95 times, 4.00 times and 5.17 times its maximum capacity aluminum beam ratio of 0%. Rated maximum bending stress concrete (FCR) are eligible crack width 0.4 mm when conditions permit loading is an aluminum beam with a ratio of 0.68%; 1.02%; 1.36% 3.81 MPa; 3.89 MPa; 4.02 MPa.